Annually Resolved Marine Climate Variability in Northern Norway from the Long-Lived Marine Bivalve Arctica islandica, August 2014 to July 2019 - Wanamaker, Alan; Retelle, Michael (Arctic Data Center, 2019)
Our major goals were to reconstruct year to year marine hydrographic variability during intervals within the last millennium along the Arctic islands of Ingoy and Rolvsoy (northern Norway). This location is sensitive to large-scale ocean circulation dynamics and is influenced by changes in the North Atlantic Current and the Norwegian Coastal Current. The strength and position of the North Atlantic Current is related to the Atlantic meridional overturning circulation, which greatly influences global climate. In order to do this research, we used the marine bivalve Arctica islandica which grows in annual layers, much like tree rings. Because these clams produce annual layers in their shells, the variability from year to year growth can be used as a “bar code” to match growth patterns between individuals. Similar to dendrochronology (tree ring research), modern specimens with known dates of collection can be matched with dead collected shell material from the same location in order to extend the shell growth series back in time. Using the method of crossdating, robust growth series can be generated when a population of clams respond to the same environmental forcings. Once a growth series is established, we sample the individual growth layers when the exact calendar year is known. The calcium carbonate powder from these shells is then analyzed for its isotopic composition. In particular, oxygen isotopes from the shell material reflect seawater temperature and is related to changes in salinity. Stable carbon isotopes in these shells can reflect productivity dynamics and can be used to track different water masses through time. Additionally, we used the radiocarbon signature from the shells to estimate the date of death. Once these shells were crossdated into our growth chronology, we could use the radiocarbon signature as a water mass tracer. In other words, at this location, we could determine if the seawater was entirely from the North Atlantic waters or if Arctic waters were present. Datasets include: the shell growth series, oxygen isotopes, carbon isotopes, and radiocarbon measurements with estimated calendar ages.